Pengaruh Desain Impeller terhadap Perilaku Hidrodinamika dan Efisiensi Penyisihan TSS serta Kekeruhan pada Proses Koagulasi Flokulasi - Maharani, Cahya Nova Putri; Rachmanto, Tuhu Agung (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Domestic wastewater pollution remains a significant environmental issue in Indonesia, characterized by high levels of Total Suspended Solids (TSS) and turbidity that exceed quality standards. One of the effective treatment methods is the coagulation flocculation process, which involves the addition of chemical coagulants, such as Poly Aluminium Chloride (PAC). This study aims to analyze the influence of hydrodynamic variables, including the presence of baffles, impeller types (paddle, turbine, and propeller), and impeller installation height, on flow patterns, floc formation, and the removal efficiency of TSS and turbidity. Experiments were conducted using a laboratory scale tank with impeller positions varied at 30–50% of the impeller diameter from the bottom of the tank. The results showed that the flow pattern within the tank was significantly affected by the impeller design and installation height, while the presence of baffles with small dimensions tended to accelerate floc breakage. The optimum condition was achieved using a turbine with four flat blades and a vaned disc, installed at a height of 3.0 cm from the tank bottom without baffles, resulting in TSS and turbidity removal efficiencies of up to 91.67% and 83.27%, respectively. This study highlights the critical role of hydrodynamic variables in enhancing the effectiveness of the coagulation flocculation process for domestic wastewater treatment.